Development and comprehensive greenness assessment of HPLC method for quality control of β-sitosterol in pharmaceutical ointments with trio-color coded evaluation - Haya I. Aljohar; Abdullah M. Al-Hossaini; Seham A. Alzammay; Samiah Alhabardi; Hadir M. Maher; Aya R. Ahmed (BMC Chemistry)
Abstract A simple, rapid, and reproducible high-performance liquid chromatography (HPLC) method has been developed and validated for the determination of β-sitosterol in the pharmaceutical dosage form of moist exposed burn ointment (MEBO). This method involved an effective sample procedure for extraction of β-sitosterol from MEBO using an alkali saponification agent composed of 0.8 N ethanolic NaOH and diethyl ether. The chromatographic separation was achieved on a C18 column (50 × 3.0 mm, 2.5 μm), using a mobile phase composed of methanol and acetonitrile (70:30 v/v) pumped in an isocratic mode at a flow rate of 0.7 mL/min. The column temperature was maintained at 40 °C, the injection volume was 10 µL, and the detection wavelength was 203 nm. Employing these conditions, the retention time was found to be 2.10 min. The developed method was validated for its specificity, linearity, accuracy, precision, the limit of detection, the limit of quantification, robustness, and solution stability based on International Council for Harmonisation (ICH) guidelines Q2 (R1). Our proposed method demonstrated superior performance compared to other reported methods. It exhibited a linearity range of 30 to 500 µg/mL and improved detectability with a limit of detection (LOD) of 4.65 µg/mL, highlighting its high sensitivity. Additionally, the separation was achieved in a remarkably short analysis time of just 2.1 min, which not only enhanced throughput but also significantly minimized waste and solvent consumption, thereby making it a more sustainable and effective alternative for β-sitosterol extraction. Moreover, in the light of green and white analytical chemistry, a comprehensive ecological and sustainable tri-color coded assessment protocol was established. The proposed method has been successfully applied to quantify β-sitosterol in commercial products (MEBO®, Avomeb® and BISTROl®) demonstrating its suitability for routine quality control analysis of β-sitosterol in pharmaceutical ointment dosage forms.